1969
DOI: 10.1136/bmj.1.5636.92
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardiac Angina: Haemodynamic Aspects and Treatment

Abstract: Summary: A patient with a sinus bradycardia and angina is described who was unable to increase his heart rate on vigorous exercise by more than a few beats. His severe angina was attributed to the bradycardia. Atrial pacing of his heart abolished his angina and increased his exercise tolerance. Circulatory changes at rest, on exertion, and with atrial pacing are described. The cause of angina in this patient is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It was suggested by Fowler et al (1969) that the pathology of sinoatrial node disorder might be comparable with that found in idiopathic heart block and indeed atrophy and fibrosis do occur in the latter condition. Furthermore, the changes detected in this series were not limited to which contains injectate, has split into 2 branches.…”
Section: Discussionmentioning
confidence: 92%
“…It was suggested by Fowler et al (1969) that the pathology of sinoatrial node disorder might be comparable with that found in idiopathic heart block and indeed atrophy and fibrosis do occur in the latter condition. Furthermore, the changes detected in this series were not limited to which contains injectate, has split into 2 branches.…”
Section: Discussionmentioning
confidence: 92%
“…Thus in 1 series, 61 per cent of patients were considered to have coronary artery disease, yet a past history of myocardial infarction was present in only 20 per cent (Hartel and Talvensaari, 1975). Presumably most of the rest were diagnosed on the basis of angina of effort, but some believe that this may itself be a manifestation of the bradycardia (Fowler et al, 1969). Postmortem coronary angiography and histological examination of the sinoatrial node should be the final arbiters.…”
Section: Discussionmentioning
confidence: 99%
“…This formula resulted in some original descriptions of disease, including printer's asthma, 1 caused by allergy to gum acacia used as a print set-off spray, and bradycardiac angina. 2 He coauthored research on the potential of the ganglion blocking agent hexamethonium to prevent heart failure 50 years before β adrenergic blocking drugs were to become routine therapy for patients with heart failure. 3 He completed his MD thesis while working with Donald Hunter on resettling disabled people.…”
mentioning
confidence: 99%